First Results of Clinical Application of Ultraviolet Corneal Collagen Crosslinking in the Treatment of Corneal and Graft Ulcers in Children - A. V. Pleskova; L. A. Katargina; E. N. Iomdina; A. Yu. Panova; I. R. Mamakaeva; A. A. Zaiceva; A. A. Sorokin (Oftalʹmologiâ)
Ulcerative lesions of the cornea and graft in children are a serious problem in pediatric ophthalmology, leading to serious consequences, up to the anatomical death of the eye. The problem of effective treatment of this pathology and corneal tissue regeneration in children remains relevant, despite the large arsenal of drugs. Recently, ultraviolet (UVA) corneal collagen crosslinking has been proposed as an alternative treatment for corneal ulcers in adults. RASK-CXL is the official name used exclusively for crosslinking in cornea inflammatory diseases. In children, corneal collagen crosslinking is still used only for the treatment of keratoconus. We were the first to use this method to treat corneal ulcers and graft ulcers in children.Purpose: to analyze the results of treatment of ulcerative corneal lesions and graft in children using a new device for local UVA crosslinking.Material and methods. For dynamic observation of patients, biomicroscopy with a fluorescein test, photo registration and optical coherence tomography of the eye anterior part were used. The procedure of local UVA crosslinking for the treatment cornea ulcerative lesions was carried out using a new device on the basis of the permission of the Ethics Committee of the National Medical Reseach Center of eye deseases named after Helmholtz of the Ministry of Health of Russia (protocol No. 56 of 21.10.2021).Results. The use of 3–5 procedures of local UVA exposure (against the background of instillations of 0.1 % riboflavin solution) lasting 5–7 minutes with an interval of 1-3 days ensured epithelization of the cornea and the graft and increased visual acuity in children.Conclusion. The first treatment results of corneal ulcers and graft in children using a new portable device for local UVA crosslinking have shown its high therapeutic efficiency and prospects for further use in clinical practice.